Activity of hippocampal neurons upon high frequency stimulation of substantia nigra in experimentally induced Parkinson's disease in rats. - Darbinyan, L. V.; Hambardzumyan, L. E.; Simonyan, K. V.; Chavushyan, V. A.; Manukyan, L. P.; Badalyan, S. A.; Sarkisian, V. H. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Rotenone is a pesticide, which causes behavioral, biochemical and morphological changes in rats and reproduces features of Parkinson's disease, including selective nigrostriatal dopaminergic degeneration. Objective. The object of the current research is to investigate the effect of rotenone on synaptic transmission in hippocampus. Results. Hippocampal СА1 and СА3 neuronal responses upon high frequency stimulation of substantia nigra (100 Hz) were recorded by in vivo extracellular recording technique. Intraperitoneal injection of rotenone caused degeneration in the hippocampus and substantia nigra of rats. Changes in the electrical activity of hippocampal neurons were found. Conclusion. Our experimental results show that rotenone exerts an inhibitory effect on synaptic transmission in hippocampal neurons.